Design and validation of an instrument to assess basic motor skills in children with Down syndrome - Cazar Morales, Carmen Sobeida; Aguilar Morocho, Elva Katherine (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this article is to design an instrument for evaluating the basic motor skills of children with Down Syndrome (DS). In order to develop this measurement tool, we began by knowing the pathological characteristics of this population, in order to accurately, concisely and realistically address each of the indicators to be evaluated. In addition, it was taken into account that each test had bright colors because it is a stimulus in the teaching and learning of students with DS. This evaluation instrument has 6 tests, which include walking, jumping, rolling, crawling, throwing, and catching tests. This article describes each of the tests with their respective measurement indicators. Once this tool was designed, 5 children with DS and other 5 without this pathology, but of the same age, were evaluated to make a correlation of the results, and it was concluded that this instrument is suitable for evaluating basic motor skills in children with DS.